Visual Identity of International Scientific Conference “Society. Integration. Education.” - Delvere, Sarma; Strode, Aina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
Logo is one of the most important symbols in identity recognition of any organisation or institution. Logo and visual identity is a set of elements demonstrating the belonging of an enterprise, a product or a service to one particular complex, at the same time giving the possibility to be distinguished amongst competitors. The aim of the article is to define the concept of working out a logotype of the conference “Society. Identity. Education.” on analysis of theoretical logotype creation basis and historical research of the conference. The author used methods of theoretical research, quantitative analysis and content analysis of conference proceedings.